PEMBERIAN EDUKASI KESEHATAN TENTANG PENCEGAHAN DIARE PADA BALITA - Yesvi Zulfiana; Irni Setyawati; Dian Soekmawaty Riezqy Ariendha; Hardaniyati (Stikes Yarsi Mataram, 2023)
Diarrhea is still the second leading cause of death in children under five years old. Less than 80% of diarrhea-related deaths occur in the first 2 years of life. In Indonesia, the morbidity and mortality rates are still high. Recurrent diarrhea in children can cause nutritional deficiencies, dehydration and cause death. The high incidence of diarrhea in children is caused by many factors, including poor sanitation, poor hygiene facilities, poor personal hygiene, such as not washing hands before, after eating and after defecating. Diarrhea in toddlers occurs because of the problem of lack of family knowledge and lack of health or cultural information. Hand washing and proper feeding is one of the efforts to prevent and risk the transmission of diarrheal diseases. The community service program carried out aims to increase public knowledge and understanding about diarrhea and its prevention efforts through hand washing. Knowledge about the prevention and management of diarrhea is important for parents to control the incidence of diarrhea in children. The method of implementation is through outreach activities to the community, especially mothers of children under five about diarrheal disease and some of its prevention efforts. Health promotion is one way to increase knowledge to prevent diarrhea and to help prevent diarrhea from causing complications or death. This activity involves mothers who have toddlers in the Dasan Kolo neighborhood. With 30 participants. The results of the activity showed that there was an increase in participants' knowledge about how to prevent diarrhea in toddlers.